Properties of oriented strand board (OSB) from Ludai and Kelempayan / Wan Mohd Nazri Wan Abdul Rahman, Jamaludin Kasim and Rahim Sudin - Wan Abdul Rahman, Wan Mohd Nazri; Kasim, Jamaludin; Sudin, Rahim (2004)
Wood innovation in manufacturer spans a very wide range of science and technology. Oriented strand board (OSB) is a new type of wood composite, which is yet to be commercially produced in Malaysia or South East Asia region. OSB is made from long thin and narrow wood strands bonded with resin and converted into panel during the hot pressing operation. This study was carried out with the objective of obtaining the mechanical (MOE, MOR and IB) and physical properties of OSB from Ludai wood and Kelempayan wood with three (3) different density and three (3) different resin content (3%, 5% and 7%). As a conclusion to the study of OSB from Ludai wood, all specimens with density of 700 Kg/m3 and 600 Kg/m with resin content of 7% show better result compared to other specimens of 500 Kg/m3 and 600 Kg/m3 which value of MOE, MOR and thickness swelling meet the minimum requirement of the British Standard (BS 5669). All OSB specimens from Kelempayan wood passed the mechanical test accept for density of 500 Kg/m3 with 3% resin content. But for physical test, only treatment of 650 Kg/m3 density and 7% resin content meet the minimum requirement of the British Standard (BS 5669). It is also conclude that density of 650 Kg/m3 and 7% resin content is the optimum treatment to make OSB from Kelempayan wood.